Propylthiouracil-induced antineutrophil cytoplasmic antibody-associated vasculitis and agranulocytosis in a patient with Graves' disease. (8th January 2020) - Tomkins, Maria; Tudor, Roxana Maria; Smith, Diarmuid; Agha, Amar
Abstract : Summary: This case is the first to describe a patient who experienced concomitant agranulocytosis and anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis as an adverse effect of propylthiouracil treatment for Graves' disease. A 42-year-old female with Graves' disease presented to the emergency department (ED) with a 2-week history of fevers, night sweats, transient lower limb rash, arthralgia, myalgia and fatigue. She had been taking propylthiouracil for 18 months prior to presentation. On admission, agranulocytosis was evident with a neutrophil count of 0.36 × 10 9 /L and immediately propylthiouracil was stopped. There was no evidence of active infection and the patient was treated with broad-spectrum antibodies and one dose of granulocyte colony-stimulation factor, resulting in a satisfactory response. On further investigation, ANCAs were positive with dual positivity for proteinase 3 and myeloperoxidase. There was no evidence of end-organ damage secondary to vasculitis, and the patient's constitutional symptoms resolved completely on discontinuation of the drug precluding the need for immunosuppressive therapy. Learning points: Continued vigilance and patient education regarding the risk of antithyroid drug-induced agranulocytosis is vital throughout the course of treatment. ANCA-associated vasculitis is a rare adverse effect of antithyroid drug use. Timely discontinuation of the offending drug is vital in reducing end-organ damage and the need for immunosuppressive therapy in drug-induced ANCA-associated vasculitis. Similarities in the pathogenesis of agranulocytosis and drug-induced ANCA-associated vasculitis may offer insight into an improved understanding of vasculitis and agranulocytosis.